HUBUNGAN ANTARA FLEKSIBILITAS DENGAN KECEPATAN RENANG PADA MAHASISWA PENDIDIKAN JASMANI UNIVERSITAS MUHAMMADIYAH SORONG - Salija Hulihulis; Agus Kurniadi; Istiyono (STKIP Subang, 2026)
This study aims to determine the relationship between flexibility and swimming speed in Physical Education students of the University of Muhammadiyah Sorong. Flexibility is one of the components of physical condition that plays an important role in supporting movement efficiency and sports performance, including swimming. The research method used is quantitative research with a correlational design. The population in this study is Physical Education students of the University of Muhammadiyah Sorong, with a sample determined using purposive sampling techniques of 30 students. The instrument used to measure flexibility was the sit and reach test, while swimming speed was measured using a 50-meter freestyle swim test. Data analysis used the Pearson Product Moment correlation test at a significance level of 0.05. The results showed that there was a significant relationship between flexibility and swimming speed (r = 0.62; p < 0.05), which suggests that the better the student's level of flexibility, the better their swimming speed. Based on these results, it can be concluded that flexibility has a strong contribution to swimming speed in Physical Education students of the University of Muhammadiyah Sorong